Welcoming Strangers: Protestant Churches’ Involvement in Refugee Resettlement in the United States - Lee, Young-Joo (Journal for the scientific study of religion, 2024)
Providing shelters and other aid for refugees is one of the core Christian principles, but there exists a great divide in Protestant churches’ response to the refugee crisis. This study examines what contributes to the divide, focusing on how various congregational characteristics relate to churches’ interests and involvement in refugee resettlement. The analysis of the 2018–2019 National Congregations Study data reveals that political conservatism within a church is linked to the disinterest in refugee resettlement. The results also show that churches with more members who have a bachelor's degree and churches participating in international humanitarian works are more likely to have discussions on refugee resettlement. In terms of direct involvement in helping refugees, congregational members’ migration experiences seem to make a significant difference.